2009
DOI: 10.1093/intqhc/mzn058
|View full text |Cite
|
Sign up to set email alerts
|

Women's satisfaction with delivery care in Nairobi's informal settlements

Abstract: Health providers should be sensitized to the finding that unintended pregnancy is associated with lower satisfaction with delivery care. Maternal health programmes should focus on increasing provider empathy, especially for women who experience complications, in both private and government health facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
104
8
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 16 publications
23
104
8
1
Order By: Relevance
“…Our finding is in line with other studies which have demonstrated that private health providers can deliver adequate health services than the public sector (Walker et al 2001;Aljunid, 1995). Yet there are other studies that contend that within the private health care delivery, industrial or urban dwellers are more satisfied than those living in a more distant and marginalized settlement (Bazant and Koenig, 2009). …”
Section: Resultssupporting
confidence: 92%
“…Our finding is in line with other studies which have demonstrated that private health providers can deliver adequate health services than the public sector (Walker et al 2001;Aljunid, 1995). Yet there are other studies that contend that within the private health care delivery, industrial or urban dwellers are more satisfied than those living in a more distant and marginalized settlement (Bazant and Koenig, 2009). …”
Section: Resultssupporting
confidence: 92%
“…The study conducted in Amhara region referral hospitals also showed women's satisfaction with delivery care was associated with wanted status of the pregnancy [AOR = 2.2,95% CI:1.2,3.93)] [25]. Those findings are in line with the study finding from Kenya, on mothers satisfaction with delivery service, the adjusted odds of satisfaction with delivery care was higher for women with a wanted pregnancy [AOR=2.75, 95% CI (1.82, 4.14)] [26]. Tough it is difficult to identify cause and effect, all these evidences show mothers who planned their pregnancy tend to have better satisfaction with delivery service they receive from health facilities.…”
Section: Discussionsupporting
confidence: 82%
“…Poor usage of care might be related to lack of provision of socioculturally appropriate and respectful care by care providers, with women identifying these services as unsuitable or inadequate (25). Women's perceived quality of care and satisfaction with maternity care is largely associated with the availability of skilled and experienced staff, polite behaviour by staff and greater provider empathy (25,26). A family-supportive environment during pregnancy and childbirth is essential to maximize favourable outcomes (27).…”
Section: Discussionmentioning
confidence: 99%